DESCRIPTION OF YOUTH SLANG AS AN INDISPENSABLE TOOL FOR MODERN SPEECH - Tatagulova, Zh.K. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
It is impossible to study a language as a social phenomenon without paying attention to its emotional component. Slang is no exception. Its main function is to convey emotional color. The relevance of the article is expressed by the naturalness and pronounced relevance and regularity of the use of slang, as an integral part of speech at the present stage of world development. Slang has become the norm in modern speech, many authors include it in their novels; films, music - everything uses new expressions. The main problem is the fact of developing slangs over time and replenishing the vocabulary every minute. It is possible to put forward such a hypothesis that it is expected that youth slang will be replenished every minute more and more, and some expressions will cease to be slang at all and will be normal, literary.
Keywords: youth slang; modern speech; emotional component; jargon; slangisms